Scientific Workflow Deployment: Container Provenance in High-Performance Computing - Kunstmann, Liliane; Pina, Débora; de Oliveira, Daniel; Mattoso, Marta (Anais do Simpósio Brasileiro de Banco de Dados (SBBD), 2024)
Deploying scientific workflows in high-performance computing (HPC) environments is increasingly challenging due to diverse computational settings. Containers help deploy and reproduce workflows, but both require more than just accessing container images. Container provenance provides essential information about image usage, origins, and recipes, crucial for deployment on various architectures or engines. Current support is limited to container actions and processes without workflow traceability. We propose extending workflow provenance to include container data using ProvDeploy, which supports workflow deployment with various container compositions in HPC, using W3C-PROV for container representation. We evaluated this with a real scientific machine learning workflow.